DAMPAK PELARANGAN PENGGUNAAN CANTRANG TERHADAP KONDISI SOSIAL EKONOMI NELAYAN TEGAL - Hendrayana Hendrayana; Ninik Umi Hartanti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
The government regulations about cantrang inhibition utilization impact on the socio-economic conditions of Tegal fishermen. The aim of the research was to determine the cantrang inhibition utilization impact on the socio-economic conditions of Tegal fishermen. The descriptive method was applied in research. The  interview  method  was  applied in  research to collected  data.  The  data collected was fisherman income, fishing operation manajemen, fishing permit and fisherman activity. Cantrang inhibition utilization impact has a  increasing of unemployment rate, change of fishing pattern, increasing of fish price and decreasing of fisheries industry. Keyword : Cantrang, Fishing, Fisherman, Sosio – Economi, Tegal